A qualitative study of the stigmatization and coping mechanisms among pregnant teenagers living with HIV in Thailand - Supalak Phonphithak; Narin Hiransuthikul; Penchan Pradubmook Sherer; Sasithorn Bureechai (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This aim of this study was to explore the experiences of stigmatization and coping mechanisms during pregnancy among pregnant women who are living with HIV in Thailand. The secondary objective was to determine factors contributing to stigma during motherhood among HIV-infected women as well as explore how they cope with the discrimination from society. Design/methodology/approach - Qualitative data were collected using in-depth interviews to obtain different versions of stigmatized experience from 16 pregnant women living with HIV on stigmatization and coping mechanisms. There were 5 pregnant adolescents living with HIV and 11 adult pregnant women living with HIV. The content analysis was used to examine patterns of stigmatizations and attributed factors. Findings - Personal stigma was found among pregnant women living with HIV regardless of age. HIV status disclosure was the crucial barrier of accessing to care for people experiencing stigmatizations. Personal stigma associated with higher HIV status was not disclosed. Interestingly, all teenage mothers who participated in this study disclosed their HIV-status to their family. People who have social support especially from family and significant others are found to be able to cope and get through the difficulties better than those who lack those social support. Originality/value - This study yields outcomes similar to several other studies that have been conducted either in Thailand or other countries. This study found that family support was crucial in reducing HIV stigma. Furthermore, HIV-infected pregnant female adults were more afraid to disclose their HIV status to their husbands, other family members and their work colleagues.